Strengthening the evidence base around prevention and management of wasting and nutritional oedema in infants and children: Insights from the 2023 WHO guideline - Daniel, Allison I.; de Polnay, Kirrily; Bendabenda, Jaden; Grummer-Strawn, Laurence; Chad, Nina J.; McCaul, Michael; Naude, Celeste E.; Weise Prinzo, Zita; Guideline Development Group on Wasting and Nutritional Oedema (BMJ, 2025)
In 2023, WHO released a guideline on prevention and management of wasting and nutritional oedema (acute malnutrition) in infants and children under 5 years as part of the Global Action Plan on Child Wasting, a consolidated framework to accelerate progress in prevention and management of wasting and nutritional oedema.